The great ideas of psychology - Robinson, Daniel N. 1937-; Teaching Company (Springfield, VA Teaching Co., 1997)
Presents forty-eight lectures tracing the development and evolution of psychology, from ancient times to the twentieth century.
Teaching Co.: 661A--664A.
In 4 containers (26 cm.).
Daniel N. Robinson, lecturer.
Keywords: Psychology -- History